Two Axes Sun Tracking System for Heliostat: Case Study in Algeria - Mihoub Sofiane; Ali Chermitti (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2016)
In this paper, using Proteus software, sun tracking system with 2 axes has developped to site of GHARDAIA, in the south of ALGERIA.O2 DC motors have used to move heliostat in N–S and E–W axis polar, in order to tracking the sun path.the distinction between day and night has provided by light dependent resistor (LDR).An algorithm of two axes sun tracking system hab developed and simulated under Proteus software, after DC motor’s parameters have verified and simulated under MATLAB software. The results show that: in the first, the development of the heliostat control requires the knowledge of the position of each heliostat relative to the tower to ensure the proper operation of the motors, and the uniformity of the reflected beam to the target.Then the choice of the drive motors is based on the useful power, including the weight of the heliostat, and all efforts affects on operation of motors in different seasons of the year, like the wind.And The position of the heliostat depends of chopper duty cycle.Finally,Conducting a power tower with mobile heliostats requires a techno-economic study on all components (heliostats, tower...) of the plant, for example weather two motors for each heliostat field.